The simple fact of the matter is, that this cannot be expressed in terms of elementary functions. You can't take the integral of this using u substitution, integration by parts, partial fractions, trigonometric identities, trigonometric substitution ... none of those methods will work, which is why you won't find a solution.
Just like
Integral (sin(x^2)dx), or
Integral (e^(x^2) dx)
Edit: My bad; math kp is correct.
x/(1 + x^3) = A/(1 + x) + (Bx + C)/(x^2 - x + 1)
Note that
x^2 - x + 1 = x^2 - x + (1/4) + 1 - 1/4
= [x - (1/2)]^2 + 3/4, so
x/(1 + x^3) = A/(1 + x) + (Bx + C)/( [x - (1/2)]^2 + 3/4 )
Taking the integral of A/(1 + x) is easy; the answer is just
A*ln|1 + x|.
The integral of (Bx + C)/( [x - (1/2)]^2 + 3/4 ), however, is another issue. Let's solve this integral by itself.
Integral ( (Bx + C)/( [x - (1/2)]^2 + 3/4 ) ) dx =
Let u = x - (1/2). Then
u + (1/2) = x, and
du = dx, so we have
Integral ( (B(u + 1/2) + C) / (u^2 + 3/4) ) du
Let's multiply everything by 4 to get rid of all fractions.
Integral ( (B(4u + 2) + C) / (4u^2 + 3) du )
Integral ( (4Bu + 2B + C) / (4u^2 + 3) du)
Let's separate this into two integrals:
Integral ( (4Bu) / (4u^2 + 3) ) du +
Integral ( (2B + C) / (4u^2 + 3) ) du
Let's solve these integrals separately.
Integral ( (4Bu) / (4u^2 + 3) ) du
Pull out the constant B.
B * Integral ( 4u / (4u^2 + 3) ) du
Multiply the 4u by 2; offset this by multiplying the outside by 1/2.
(1/2)B * Integral (8u / (4u^2 + 3) ) du
Now, this is an easy integral to solve.
(1/2)B * ln |4u^2 + 3|
But u = (x + (1/2)), so we have
(1/2)B * ln |4(x + 1/2) + 3|
(1/2)B * ln |4x + 2 + 3|
(1/2)B * ln |4x + 5|
Now for this integral:
Integral ( (2B + C) / (4u^2 + 3) ) du
If we pull out the constant 2B + C, we get
(2B + C) Integral ( 1 / (4u^2 + 3) ) du
We have to use trigonometric substitution on this.
Let u = sqrt(3)/2 tan(t)
du = sqrt(3)/2 sec^2(t) dt
(2B + C) Integral ( {1 / [3tan^2(t) + 3] } sqrt(3)/2 sec^2(t) } dt)
[sqrt(3)/2] (2B + C) Integral ( {1 / 3sec^2(t)} sec^2(t) dt)
[sqrt(3)/2] (2B + C) Integral ( {1/3} ) dt =
[sqrt(3)/2] (2B + C) [t/3]
But u = [sqrt(3)/2 tan(t)], so it follows that
[2/sqrt(3)]u = tan(t), and
t = tan^(-1) ([2/sqrt(3)]u), so our answer is
[sqrt(3)/2] (2B + C) [1/3] tan^(-1) ([2/sqrt(3)]u)
Which we can simplify to
[sqrt(3)/6] (2B + C) tan^(-1) ([2/sqrt(3)]u)
But u = [x + (1/2)], so we have
[sqrt(3)/6] (2B + C) tan^(-1) ( [2/sqrt(3)] (x + (1/2) )
Whew! Tall order! Let's combine everything we have now
Integral ( x / (1 + x^3) ) dx =
A*ln|1 + x| + (1/2)B * ln |4x + 5| + [sqrt(3)/6] (2B + C) tan^(-1) ( [2/sqrt(3)] (x + (1/2) )
And guess what? We're not even done, because we have to solve for A, B, and C.
x/(1 + x^3) = A/(1 + x) + (Bx + C)/(x^2 - x + 1)
But 1 + x^3 = (1 + x) (x^2 - x + 1), so
x/[(1 + x)(x^2 - x + 1)] = A/(1 + x) + (Bx + C)/(x^2 - x + 1)
Multiply both sides by (1 + x)(x^2 - x + 1),
x = A(x^2 - x + 1) + (Bx + C)(1 + x)
This is true for all x, so let x = -1. Then
-1 = A(1 + 1 + 1) + 0
-1 = A
We can derive B and C by expanding the right hand side of that equation.
x = Ax^2 - Ax + A + Bx + Bx^2 + C + Cx
x = Ax^2 + Bx^2 + Bx - Ax + Cx + A + C
x = (A + B)x^2 + (B - A + C)x + (A + C)
This give us the equations
B - A + C = 1
A + C = 0
But we know the value of A; A = -1, so C = 1.
Consequently, plugging in A = -1 and C = 1 for B - A + C = 1,
B - (-1) + (1) = 1
B = 1.
Therefore, A = -1, B = 1, C = 1
That makes our final answer
-ln|1 + x| + (1/2) * ln |4x + 5| + [sqrt(3)/6] (3) tan^(-1) ( [2/sqrt(3)] (x + (1/2) )
Or, reducing this
-ln|1 + x| + (1/2) * ln |4x + 5| + [sqrt(3)/2] tan^(-1) ( [2/sqrt(3)] (x + (1/2) ) + C
2007-01-30 21:15:30
·
answer #1
·
answered by Puggy 7
·
0⤊
0⤋
This is not as difficult as others make it out
you can put x/(1+x^3) = A/(1+x) +(Bx+C)/(1-x+x^2)
u can now aolve for A , B and C and then integrate
2007-01-30 21:34:59
·
answer #2
·
answered by Mein Hoon Na 7
·
1⤊
0⤋
The simplest method you can try is to find the McLaurin expansion for the given expression and integrate term by term.
OR break int partial fractions!
2007-01-30 21:45:38
·
answer #3
·
answered by yasiru89 6
·
0⤊
0⤋
I wish I knew.
Just a suggestion... You're losing points. You lose 5 points each time you ask a question, but you receive 2 points for each one you answer. Soooo, you might want to answer at least 3 questions for each one you ask, so at least your points will go UP and not down.
Maybe once a week you can just answer several questions, or enough to keep a good supply of points on hand for the questions you intend to ask.
.
.
2007-01-30 20:58:24
·
answer #4
·
answered by OhWhatCanIDo 4
·
0⤊
1⤋